Production, purification, and characterization of an extracellular acid protease from the marine Antarctic yeast Rhodotorula mucilaginosa L7 - Lario, Luciana Daniela; Chaud, Luciana; Almeida, María das Graças; Converti, Attilio; Durães Sette, Lara [UNESP]; Pessoa, Adalberto (Elsevier B. V., 2015)
The production, purification, and characterization of an extracellular protease released by Rhodotorula mucilaginosa L7 were evaluated in this study. This strain was isolated from an Antarctic marine alga and previously selected among others based on the capacity to produce the highest extracellular proteolytic activity in preliminary tests. R. mucilaginosa L7 was grown in Saboraud-dextrose medium at 25 °C, and the cell growth, pH of the medium, extracellular protease production and the glucose and protein consumption were determined as a function of time. The protease was then purified, and the effects of pH, temperature, and salt concentration on the catalytic activity and enzyme stability were determined. Enzyme production started at the beginning of the exponential phase of growth and reached a maximum after 48 h, which was accompanied by a decrease in the pH as well as reductions of the protein and glucose concentrations in the medium. The purified protease presented optimal catalytic activity at pH 5.0 and 50 °C. Finally, the enzyme was stable in the presence of high concentrations of NaCl. These characteristics are of interest for future studies and may lead to potential biotechnological applications that require enzyme activity and stability under acidic conditions and/or high salt concentrations.
Keywords: Cold-adapted yeast; Enzyme characterization; Extracellular protease